The Relationship Between Renewable Energy, Agriculture And Carbon Emissions: The Case of Turkey - Kapçak, Servet; Işleyen, Sakir (Border Crossing, 2024)
In this study, the relationship between renewable energy consumption, agriculture, and carbon emissions (CO2) is investigated. Time series boundaries cover the period 1990-2019 for Turkey. Economic growth and urbanization were added to the model as explanatory variables. The prediction model has been tested by the ARDL boundary value test and the direction of the variables is determined by the Granger(1969) causality test. The findings show that the variables are cointegrated in the long term and that while renewable energy consumption reduces carbon emissions, the agricultural sector increases carbon emissions. According to another finding, economic growth and urbanization variables have a positive effect on carbon emissions. Finally, a one-way relationship between the agricultural sector and economic growth to carbon emission has been identified. On the other hand, a one-way causality has been found between renewable energy consumption in the agricultural sector and urbanization. In addition, it has been found that there is a bidirectional causality between urbanization and urbanization and between economic growth and urbanization. These results show that renewable energy consumption, the agriculture sector, and carbon emissions interact in Turkey.